2015
DOI: 10.3892/etm.2015.2658
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinases in radiation-induced lung injury in alveolar epithelial cells of Bama minipigs

Abstract: Abstract. Radiation-induced lung injury (RILI) is a common complication associated with thoracic radiotherapy. The aim of the present study was to investigate the effects of a single 15-Gy dose of right-thoracic lung irradiation on the expression levels of matrix metalloproteinases (MMPs) and other proteins in the alveolar epithelial type II (AE2) cells of Bama minipigs. All minipigs received either right-thoracic irradiation or sham irradiation under anesthesia, and were sacrificed at 4, 8, 12 or 24 weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
3
9
0
Order By: Relevance
“…MMPs degrade ECM that facilitates angiogenesis, tumour cell invasion, and metastasis [ 262 ]. IR also promotes MMP-2/9 activation in cancer cells to promote EMT, invasion, and metastasis [ 54 , 106 , 263 266 ]. IR enhances MMP-2 transcription and protein secretion by activating the EGFR/p38/Akt and EGFR/PI3K/Akt signalling pathways, which enhance the invasion of glioma cells [ 106 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs degrade ECM that facilitates angiogenesis, tumour cell invasion, and metastasis [ 262 ]. IR also promotes MMP-2/9 activation in cancer cells to promote EMT, invasion, and metastasis [ 54 , 106 , 263 266 ]. IR enhances MMP-2 transcription and protein secretion by activating the EGFR/p38/Akt and EGFR/PI3K/Akt signalling pathways, which enhance the invasion of glioma cells [ 106 ].…”
Section: Introductionmentioning
confidence: 99%
“…IR also increases MMP-9 expression by activating the PI3K/Akt/NF-κB pathway, which enhances hepatocellular carcinoma cell invasion [ 263 ]. IR-induced MMP-2/MMP-9 expression not only degrades ECM proteins, but also cleaves latent TGF-β1 to activate the TME [ 266 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…large number of pro-inflammatory and fibrotic cytokines induced by thoracic radiotherapy can also cause acute and delayed injury to the lung tissue. [3][4][5] It is known that molecules, such as tumor necrosis factor-(TNF-), transforming growth factor-1, interleukin-1 (IL-1), interleukin-6 (IL-6), and interferon-, and changes in their gene expression are involved in the initiation and development of RP. [6][7][8][9] Serum amylase A (SAA), an acute phase response protein, has been reported to be Prec.…”
Section: 2 Amentioning
confidence: 99%
“…RP is commonly considered to be a complex inflammatory process involving a series of cytokines and adhesion molecules mediated by lung parenchymal cells and circulating immune cells . A large number of pro‐inflammatory and fibrotic cytokines induced by thoracic radiotherapy can also cause acute and delayed injury to the lung tissue …”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 12 ] It is reported that MMP-2 activity is associated with the collagen deposition and the formation of subretinal deposit. [ 13 , 14 ] It has been identified that the expression level of MMP-2 is upregulated in choroidal neovascularization in animal model. [ 15 ] The study performed by Hussain et al [ 16 ] suggested that the total level of pro-MMP-2 was raised in AMD.…”
Section: Introductionmentioning
confidence: 99%